TRANSFORMASI NILAI-NILAI SPIRITUAL DALAM BUDAYA ORGANISASI PADA SEKOLAH BERPRESTASI DI KOTA MALANG - Marno Marno (lp2m-uin malang, 2010)
Achievement or added values of an educational institution is higly influenced by invisible (soft) dimensions in the form of organization culture values, which comprise values, beliefs, cultures and behavior norms. These values can give spirit to the work of organization through transformation process as a changing step of the reflection or internalization of spiritual values. This, in turn, becomes individual and organizational values of an educational institution which can produce an outcome in the form of school organization culture, that is behavior or customs performed by the members of the organization consistently in solving various problems.